Recent harbour porpoise bycatch in gillnet fisheries in Newfoundland and Labrador, Canada - Benjamins, Steven; Lawson, Jack; Stenson, Garry (J. Cetacean Res. Manage., 2023)
Despite reduced fishing effort in many North Atlantic fisheries following collapse of fish stocks, concerns remain about levels of direct mortality of harbour porpoise (Phocoena phocoena), primarily through incidental catches in fishing gear. Although harbour porpoise incidental catch is known to occur in several fisheries along the coast of Newfoundland and Labrador, Canada, there are no reliable quantitative estimates for the last decade when the commercial fisheries have undergone major changes in effort and target species. Based on incidental catch rates derived using different reporting methods, with net-days as measures of effort and fishing trips as sampling units, the potential number of incidental catches of harbour porpoises in several gillnet fisheries in Newfoundland waters was estimated for the years 2001, 2002 and 2003. Confidence intervals were calculated using re-sampling techniques. Incidental catches of small cetaceans were estimated to be 862 in 2001, 1,428 in 2002 and 2,228 in 2003 in Newfoundland gillnet fisheries; virtually all cetaceans reported were harbour porpoises. Annual estimates of incidental catch of small cetaceans varied greatly between fisheries and areas. Confidence intervals were large due to variation in reported incidental catch rates among individual fishers and geographic areas. Most small cetaceans were reported in the nearshore cod fishery, although there were also numerous reports of catches in nearshore fisheries for lumpfish, herring and Greenland halibut. Incidental catch of small cetaceans was also identified in offshore fisheries for monkfish, white hake and Greenland halibut. Most incidental catch events occurred during the third quarter of the year (July-September) along the south coast, although catches of harbour porpoises were also reported during the second and fourth quarters. Several strategies could be implemented to better monitor small cetacean incidental catch in Newfoundland and Labrador waters. However, harbour porpoise population estimates are required before it can be determined if this fisheries-related mortality occurring in Newfoundland is sustainable.